2010
DOI: 10.1097/mop.0b013e32833b7c23
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia in children and adolescents

Abstract: Purpose of the review-In this review we define hypercalcemia levels, common etiologies for hypercalcemia in children, and treatment in order to aid the practicing pediatrician.Recent Findings-One rare cause of hypercalcemia in the child is Familial hypocalciuric hypercalcemia (FHH) [also termed familial benign hypercalcemia (FBH)]. Mutations that inactivate the Ca 2+ -sensing receptor gene FHH have been described as an autosomal dominant disorder, but recently milder mutations in the CASR have been shown to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
125
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 60 publications
3
125
1
8
Order By: Relevance
“…High calcium intake rarely results in hypercalcemia in the adult and usually occurs in patient with concomitant chronic kidney disease and a significant decrease in calcium excretion. In contrast, in the small infant, hypercalcemia can occur with ingestion of calcium-enriched formulas [4].…”
Section: Case Continuedmentioning
confidence: 99%
See 4 more Smart Citations
“…High calcium intake rarely results in hypercalcemia in the adult and usually occurs in patient with concomitant chronic kidney disease and a significant decrease in calcium excretion. In contrast, in the small infant, hypercalcemia can occur with ingestion of calcium-enriched formulas [4].…”
Section: Case Continuedmentioning
confidence: 99%
“…The vitamin D supplement purchased online was a concentrated form containing 400 IU per drop. A previously published report of a similar vitamin D overdose [4] demonstrated that 1 mL was equivalent to approximately 30 drops; the patient was therefore receiving roughly 30 times the intended daily dose of vitamin D (12,000 IU per day) for approximately 1 month. According to the Institute of Medicine, the level above which there is risk for adverse events in the neonate (0-6 months of age) is 1,000 IU per day [6].…”
Section: Case Continuedmentioning
confidence: 99%
See 3 more Smart Citations